Marketing Strategies for Tourism along the Yunnan Section of the China-Laos Railway - Deng, Shijie; Bi, Chuanchen (Technium Social Sciences Journal, 2025)
As a core corridor of the Pan-Asian Railway, the full operation of the China-Laos Railway has restructured the logistics network of the Indochina Peninsula and reshaped Yunnan’s tourism economic landscape, driving the integrated development of cross-border cultural tourism. The railway has significantly enhanced transportation accessibility along Yunnan’s route, stimulated short-distance tourism demand, and spurred development in traditionally non-hotspot regions, while facing challenges such as insufficient resource integration and ambiguous branding. This study employs qualitative research methods to examine the current tourism conditions and the optimization of marketing strategies for cities along the Yunnan section of the China-Laos Railway. Findings reveal that the railway has profoundly restructured Yunnan’s tourism economic landscape, forming an integrated tourism economic belt that combines natural ecology, cultural heritage, and cross-border resources. Cities along the route, including Kunming, Yuxi, Pu’er, and Xishuangbanna, have experienced varying degrees of tourism development opportunities. The proposed 4P marketing strategies include: a product strategy centered on "high-speed rail + culture" thematic routes; a pricing strategy balancing supply-demand dynamics through dynamic pricing and bundled offers; a channel strategy emphasizing dual-channel coordination between digital platforms and physical service outlets; and a promotion strategy focused on content marketing and precision targeting. These strategies aim to transform the China-Laos Railway from a transportation artery into a "cross-regional cultural tourism economic corridor," injecting new momentum into regional sustainable development.